Evaporative cooling systems for swine - Ames, D.R.; Nichols, David A.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
During heat stress swine must rely an evaporation as a mechanism for heat loss. Providing water via sprinklers, showers, and foggers is a practical method of reducing heat stress. It is imperative in any evaporative system that animals are permitted to dry, because the evaporation of water is fundamental to evaporative cooling. Ideally, hogs should be wetted and then given time to dry, followed by successive wetting and drying. Studies are under way to investigate various systems of wetting hogs to take maximum advantage of evaporative cooling.
Keywords: Swine; Cooling systems; Evaporation; Heat stress